Influcene of Recovery on Plastic Anisotropy of Metals - Socha, G. (Engineering Transactions, 1997)
The paper describes experimental investigations of plastic anisotropy changes during recovery of plastically deformed metals. Two materials differing in crystallographic structure and manufacturing processes were investigated by means of uniaxial tests: aluminium alloy PA6 and mild steel denoted as 45 according to Polish Standards. Additionally, changes of the strain of previously deformed and unloaded material and the influence of the dynamic recovery on the shape of stress-strain curve for cyclic loading of the material were investigated. All tests were performed at room temperature. The first experiment showed that plastic anisotropy of deformed and then unloaded material begins to change immediately after plastic deformation. The changes of anisotropy parameters k, αx and Δk were shown as the functions of recovery time. Additionally, the changes of plastic anisotropy were shown in the form of cross-section of the yield surface with the plane σ x - r xy in the stress space. The second experiment showed that the strain of uniformly plastically deformed and unloaded material changes after unloading. The last experiment showed that the shape of the stress-strain curve is influenced by dynamic recovery of the material.